Overcoming Obstacles: Challenges of Gender Inequality in Undergraduate ICT Programs Extended Abstract – CTDGSI 2025 - Souza, Angelica P.; Rocha, Larissa (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2025.246771, 2025)
Gender inequality in Information and Communication Technology (ICT) programs is a persistent issue, particularly in Brazil, where women represent less than 18% of ICT students. This study explores the perceptions of 402 women enrolled in ICT undergraduate programs across 18 Brazilian states. Using a mixed-method approach, we identify key challenges such as discriminatory practices, gender stereotypes, and lack of representation, which undermine women’s confidence and participation. Findings reveal that women face interruptions, isolation, and mistrust in academic settings, often leading to course discontinuation. Strategies to improve women’s confidence and retention include increasing representation, fostering supportive environments, and raising awareness about gender biases.